A case study of collapses at the Yangshan tunnel of the Coal Transportation Channel from the Western Inner Mongolia to the Central China. (October 2019) - Liu, Fei; Ma, Tianhui; Tang, Chun'an; Liu, Xingzong; Chen, Feng
Abstract: Collapse is one of the most frequent and catastrophic hazards in tunnel engineering, which poses serious threats to the safety of personnel and great influence on the excavation schedule. This study presents the geotechnical study carried out after two violent collapses at the Yangshan tunnel of the Coal Transportation Channel from the Western Inner Mongolia to the Central China on July 2, 2017 and July 24, 2017, respectively. The in-situ stresses were first measured by a hydraulic fracturing test close to the first collapse area, and then a comprehensive investigation was conducted to study the causes of the collapses, i.e., the highly concentrated deviatoric stress at the shallow roof and the primary support parameters at the collapse areas. The microseismic (MS) monitoring technique was employed to study the progressive failure process of the surrounding rock mass and to warn of the geological hazard at the Yangshan tunnel. An active MS event zone at the Yangshan tunnel was identified by analyzing the spatial-temporal distribution and event density contour of the 303 recorded MS events, which was in good agreement with the cracking and spalling of the surrounding rock mass. The cracks at the crown in the axial direction were identified as tensile failures of the surrounding rock mass, because most of the events at the shallow roof registered the ratio of S-wave energy to P-wave energy less than 10. The average energy level gradually increased to an extremely high level was recognized as a precursor to the macroscopic cracking of the surrounding rock mass, and the collapse hazard at the Yangshan tunnel may be predicted by quantitative interpretation of the MS data. This study is valuable to understand the collapse hazard of tunnels characterized by high horizontal in-situ stresses and provide a method to warn of the failures.